2021
DOI: 10.1002/aocs.12568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aroma, aroma‐active, and phenolic compounds of crude and refined hazelnut oils

Abstract: Hazelnut (Corylus avellana L.) is an important shelled nut with its pleasant aroma. The refining process causes significant changes in the quality attributes of hazelnut oil. The aim of this study was to assess the aroma, aroma‐active, and phenolic compounds of the crude and refined hazelnut oils by using gas chromatography–mass spectrometry (GC–MS), GC–MS‐olfactometry (GC–MS‐O), and liquid chromatography–mass spectrometry (LC–MS/MS). The antioxidant capacities were also determined by DPPH and ABTS methods. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…During processing, especially in heat treatment, flavor constituents are often degraded or evaporated, causing a deterioration in product quality that may not be accepted by consumers. In the 2022 study by Kesen, S. et al, it was observed that the refining process reduced the amounts of aroma constituents by about eight times [33].…”
Section: What It Contains and What Properties It Possessesmentioning
confidence: 99%
“…During processing, especially in heat treatment, flavor constituents are often degraded or evaporated, causing a deterioration in product quality that may not be accepted by consumers. In the 2022 study by Kesen, S. et al, it was observed that the refining process reduced the amounts of aroma constituents by about eight times [33].…”
Section: What It Contains and What Properties It Possessesmentioning
confidence: 99%
“…Türkiye is the largest producer and exporter country of various types of hazelnuts in the world, contributing to approximately 70% of the total world production. Among the 18 hazelnut varieties grown in Türkiye; these hazelnuts are classified as premium quality due to its high oil content, unique taste, and aroma [1] Different aroma extraction methods were used successfully in the seeds [2]. Taste and aroma of hazelnut extracts are caused by their taste-active components (free amino and phenolic acids, sugars, organic acids, and condensed tannins) and aroma-active components (ketones, aldehydes, pyrazines, alcohols, aromatic hydrocarbons, furans, pyrroles, terpenes, and acids) [1].…”
mentioning
confidence: 99%